„Gazeta Kościelna" (1843-1849) i „Tygodnik Kościelny" (1850), czyli druga i trzecia inicjatywa czasopiśmiennicza Jana Nepomucena Jabczyńskiego - Lenort, Feliks (Ecclesia. Studia z Dziejów Wielkopolski, 2013)
The history of church journalism in Poznań begins in 1836 with the quarterly „Archiwum Teologiczne", which appeared for only two years. Its initiator and editor, Fr. Jan Nepomucen Jabczyński opened two subsequent titles: „Gazeta Kościelna" (1843-1849) and „Tygodnik Kościelny" (1850). They were weeklies and were addressed to a broader audience. They are valuable sources of information on church life especially in the archdiocese of Poznań and Gniezno.